IMPLEMENTASI PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DALAM KEPAILITAN DITINJAU DARI UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Dewi, Putu Eka Trisna (Jurnal Hukum Saraswati (JHS), 2019)
Postponement of Debt Payment Obligations(PKPU) is regulated in Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. PKPU is an inseparable matter in the bankruptcy process. PKPU can also be understood as a certain period of time given to debtors and creditors determined by a commercial court decision to make a joint agreement related to the payment or settlement of debt problems between the parties, both all or part of the debt also the possibility of debt restructuring. The methodology in this paper uses library research with a statute approach. PKPU is requested if the debtor is unable or estimates that he will not be able to continue paying his debts which have fallen due in reaction to the request for bankruptcy filed by his creditors.